1986
DOI: 10.1016/s0025-6196(12)62641-x
|View full text |Cite
|
Sign up to set email alerts
|

Papillary Thyroid Cancer Treated at the Mayo Clinic, 1946 Through 1970: Initial Manifestations, Pathologic Findings, Therapy, and Outcome

Abstract: We performed a retrospective study of 859 patients with papillary thyroid cancer, who had received their primary treatment at the Mayo Clinic during the period 1946 through 1970. The maximal follow-up was 39 years. All but 2 patients underwent a thyroid operation; 319 (37%) had metastatic cervical nodes. Of the 800 patients without distant metastatic lesions on initial examination who underwent a potentially curative surgical procedure, postoperatively 7% had nodal metastatic lesions, 6% had a local tumor recu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

32
309
8
18

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 518 publications
(367 citation statements)
references
References 40 publications
32
309
8
18
Order By: Relevance
“…Our findings revealed that low risk group had better prognosis than intermediate and high risk. This result was similar to many publish studies (McConahey et al, 1986;Gemsenjager et al, 2001;Falvo et al, 2005;Lang et al, 2006).…”
Section: Discussionsupporting
confidence: 92%
“…Our findings revealed that low risk group had better prognosis than intermediate and high risk. This result was similar to many publish studies (McConahey et al, 1986;Gemsenjager et al, 2001;Falvo et al, 2005;Lang et al, 2006).…”
Section: Discussionsupporting
confidence: 92%
“…Although most of the patients in our study received treatment that included nearly total thyroidectomy with lymph node dissection, post-operative 131I treatment and one-fifth of these patients received external radiotherapy, 7% of the patients still died of thyroid cancer. The ratio of papillary thyroid cancer with ETE and the mortality rate of patients with ETE in our study was close to that in the series from Mayo Clinic [14] and Mazzaferri et a1. [11].…”
supporting
confidence: 90%
“…Lymphatic metastases develop in 30%-90% of PTC patients, depending not only on the actual pathological stage of the disease but also on which diagnostic modalities are employed to assess the potential metastases [18][19][20]. Several reports have emphasized that although lymphatic metastasis does not affect overall survival in PTC patients, cervical LND can improve locoregional control [3][4][5]18]. Therefore, the control of regional metastasis in PTC is a major prognostic factor.…”
Section: Discussionmentioning
confidence: 99%
“…Cervical LN metastasis is the most significant prognostic factor for locoregional recurrences in patients with PTC [3][4][5]. However, cervical LN metastasis in such patients does not necessarily have an adverse affect on overall survival [2,6,7].…”
Section: Methodsmentioning
confidence: 99%